2023
DOI: 10.1158/1055-9965.epi-22-1111
|View full text |Cite
|
Sign up to set email alerts
|

Racial Differences in Breast Cancer Therapeutic Toxicity: Implications for Practice

Abstract: Disparities in treatment intensity can contribute to racial disparities in overall breast cancer survival. A natural extension of measuring racial disparities in treatment intensity is consideration of the distribution of treatment toxicities, symptoms, and distress that lead to chemotherapy dose reductions, holds or early termination. There is growing evidence that therapeutic toxicity during early-stage breast cancer treatment may be greater among Black women than White. Important components of symptom manag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 14 publications
0
1
0
Order By: Relevance
“…To punctuate our findings, the rates of AEs in AA patients were globally higher than those in W patients, but the differences were small. However, we hypothesize that differences in AEs or perceived AEs by caregivers can result in differences in treatments that impact outcomes, as suggested previously [36]. It is likely that as more and more private oncology practices integrate into hospital-owned systems, the trends we observed in lesser treatment in the AA population in the NCH setting will begin to shift to the trend we see in the Outpatient database, where AA patients actually have higher rates of treatment and more equivalent rates of AEs.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…To punctuate our findings, the rates of AEs in AA patients were globally higher than those in W patients, but the differences were small. However, we hypothesize that differences in AEs or perceived AEs by caregivers can result in differences in treatments that impact outcomes, as suggested previously [36]. It is likely that as more and more private oncology practices integrate into hospital-owned systems, the trends we observed in lesser treatment in the AA population in the NCH setting will begin to shift to the trend we see in the Outpatient database, where AA patients actually have higher rates of treatment and more equivalent rates of AEs.…”
Section: Discussionmentioning
confidence: 65%
“…Treatment-induced AEs impose significant obstacles to tolerating therapy, quality of life, and the ability to administer adequate therapy, a factor that affects outcomes [35]. A large retrospective review of 12 published articles from four large databases concluded that AAs were significantly more likely to delay the initiation of therapy, to have dose-density reductions, and to discontinue treatment than W patients with early-stage BC [36]. This has been attributed to differences in the trigger points applied by treating oncologists to reduce or change drugs or stop treatment, or to differences in the frequency of AEs in different circumstances [36].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, minority women in our study disproportionately experienced larger decreases in physical QOL after ALND, although the reason for this disparity is unclear. Studies have reported that racial minorities may experience more chemotherapy toxicity 21,22 or more severe radiation fibrosis, 23,24 which may also contribute to more troublesome arm symptoms and worse QOL. In addition, shoulder dysfunction and range-of-motion limitations after ALND, which were not di-rectly captured in our study, may also contribute to QOL reductions that may vary by race and ethnicity.…”
Section: Discussionmentioning
confidence: 99%
“…Table 1 summarizes clinicopathological characteristics of the cohort stratified by race and ethnicity. Compared with Asian and White women, Black and Hispanic women had a higher baseline BMI (median [IQR], 30 [26][27][28][29][30][31][32][33][34] and 28 [23][24][25][26][27][28][29][30][31][32] vs 23 [21][22][23][24][25][26][27][28][29] and 26 [22][23][24][25][26][27][28][29][30], respectively; P < .001), higher clinical nodal stage at presentation (clinical nodal positivity, 83% and 87% vs 60% and 72%, respectively; P = .03), and higher rates of objective lymphedema (40% and 39% vs 17% and 21%; P = .02). Additionally, Black women were less likely than other racial or ethnic groups to have private insurance (46% vs ≥70% for the other 3 groups; P < .001).…”
Section: Clinicopathological Characteristicsmentioning
confidence: 99%